Future access enablers for ubiquitous and intelligent infrastructures : third international conference, FABULOUS 2017, Bucharest, Romania, October 12-14, 2017, Proceedings /: third international conference, FABULOUS 2017, Bucharest, Romania, October 12-14, 2017, Proceedings. (2018) - Unknown
No abstract available